Name-bearing types of butterflies (Lepidoptera, Papilionoidea), in the National Museums of Scotland, Edinburgh - Bland, Keith P. (Zootaxa, 2019)
This article documents 91 species-group names of Butterflies (Lepidoptera: Papilionoidea) for which either primary or secondary type material is present in the collections of the National Museums of Scotland, Edinburgh. The describers and the 76 nominal taxa they descibed are as follows: H. Druce (1846–1913) Euphaedra COOKSONI, Mycalesis HAROLDI; H.H. Druce (1869–1922) Cyclopides COOKSONI, Spindasis KALLIMON; H.J. Elwes (1846–1922) Parnassius delphius ssp. INFERNALIS; J.C. Fabricius (1745–1808) Papilio COCALIA (“neotype”), Papilio MARDANIA (“neotype”); H. Fruhstorfer (1866–1922) Parnassius mnemosyne ssp. MELAINA; D.R. Gifford (1918–1981) Leptomyrina HANDMANI, Alaena LAMBORNI, Deudorix (Virachola) MAGDA, Papilio ophidicephalus ssp. MKUWADZI; J.B. Godart (1775–1825) Idea AGELIA, Danais ALCATHOE, Cethosia ALIPHERA, Danais ALOPIA, Danais BAUDINIANA, Papilio BITIAS, Argynnis BRIAREA, Heliconia CLEOBAEA, Danais CLEOPHILE, Danais CLEOTHERA, Heliconia CYRBIA, Pieris DOXO, Pieris EPICHARIS, Pieris ERIPHIA, Heliconia ETHILLA, Heliconia EUCLEA, Papilio EURYMAS, Pieris GIDICA, Argynnis HEGEMONE, Satyrus HYSIUS, Papilio IMERIUS, Acraea JANISCA, Pieris JOSEPHINA, Vanessa LAODORA, Papilio LEUCASPIS, Papilio LYCORAEUS, Vanessa LYTREA, Heliconia MEGARA, Heliconia MELPHIS, Libythea MYRRHA, Acraea OZOMENE, Pieris PHISADIA, Papilio POLYMETUS, Danais PROTHOE, Argynnis PYGMAEA, Pieris PYRO, Pieris SALACIA, Acraea SERVONA, Papilio TEMENES, Papilio TEREAS, Libythea TERENA, Biblis THADANA, Argynnis THAROSSA, Papilio TRIOPAS, Pieris VENILIA, Vanessa VULCANIA, Acraea ZETHEA, Acraea ZIDORA, Acraea ZOSTERIA; C.W.N. Holmes (1916–2018) Bebearia paludicola ssp. BLANDI, Bebearia cocalioides ssp. HECQI, Bebearia orientis ssp. MALAWIENSIS, Bebearia PALUDICOLA; E.G. Honrath (1837–1893) Parnassius bremeri ssp. GRAESERI, Parnassius nordmanni var. MINIMA; W.J. Kaye (1875–1967) Hesperocharis LAMONTI; F. Moore (1830–1907) Neptis ADARA, Abisara ANGULATA, Lebadea ATTENUATA, Ixias CITRINA, Euploea LIMBORGII, Papilio ONPAPE, Cirrhochroa SURYA; W.F.H. Rosenberg & G. Talbot (1914) Dismorphia orise ssp. DENIGRATA.        The secondary type material (number of species in brackets) originates from H. Carcasson (1), M. Cock (1), J. B. Godart (7), W. J. Kaye (1), O. Kudrna (3) and M. B. Usher (2).